Pengaruh Efektifitas Pengendalian Internal dan Pengembangan Mutu karyawan terhadap Deteksi Kecurangan (Fraud) - Deni Raharjo Nyoto Susanto; Moch Nafi (University of Merdeka Malang, 2021)
The research aimed at analyzing internal effectiveness and developing analysis of fraud detection. The technique used was multiple linear regression analysis with the stages of descriptive statistical tests and data analysis. To analyze the data consisted of validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, variable t hypothesis, determination test, and hypothesis test f. The results showed that partially and simultaneously each was independent, namely the effectiveness of internal control and development. quality has a significant and positive effect on the fraud examination variable.